Molecular Design of Non‐doped OLEDs Based on a Twisted Heptagonal Acceptor: A Delicate Balance between Rigidity and Rotatability. (11th February 2020) - Huang, Zhenmei; Bin, Zhengyang; Su, Rongchuan; Yang, Feng; Lan, Jingbo; You, Jingsong
Abstract: The development of efficient non‐doped organic light‐emitting diodes (OLEDs) is highly desired but very challenging because of a severe aggregation‐caused quenching effect. Herein, we present a heptagonal diimide acceptor (BPI), which can restrict excessive intramolecular rotation and inhibit close intermolecular π–π stacking due to well‐balanced rigidity and rotatability of heptagonal structure. The BPI‐based luminogen (DMAC‐BPI ) shows significant aggregation‐induced delayed florescence with an extremely high photoluminescence quantum yield (95.8 %) of the neat film, and the corresponding non‐doped OLEDs exhibit outstanding electroluminescence performance with maximum external quantum efficiency as high as 24.7 % and remarkably low efficiency roll‐off as low as 1.0 % at 1000 cd m −2, which represents the state‐of‐the‐art performance for non‐doped OLEDs. In addition, the synthetic route to DMAC‐BPI is greatly streamlined and simplified through oxidative Ar−H/Ar−H homo‐coupling reaction. Abstract : Drehwurm in der OLED : Ein verdrehter heptagonaler Diimid‐Akzeptor mit gut ausgewogener struktureller Rigidität und Drehbarkeit wurde für die Synthese eines hoch effizienten Materials entwickelt, das aggregationsinduzierte verzögerte Fluoreszenz zeigt und zur Herstellung hochmoderner, leistungsfähiger, nicht‐dotierter organischer Leuchtdioden (OLEDs) eingesetzt wurde.